EFFECICACY OF DIFFERENT INSECTICIDES FOR THE CONTROL OF APHID, BREVICORYNE BRASSICAE (LINN.) (HOMOPTERA; APHIDIDAE) ON CANOLA, BRASSICA NAPUS (L.) - Aslam, Muhammad; Razaq, Muhammad; Zafar-Ul-Islam; Anjum, Shazad (Journal of Research (Science), 2001)
Effectiveness of Imidacloprid 25WP @250 gm/ha, Cabosulfan 20EC @1800 ml/ha, Triazophos 40EC @1400 ml/ha and Imidacloprid 200SL @ 600 ml/ha was studied for the control of aphid, Brevicoryne brassicae (Linn.) on canola, Brassica napus at Multan, Pakistan during crop season 1998-99, at pod formation stage. All the insecticides gave effective control of the aphids up to nine days after application, but Triazophos proved to be the best because of its consistent effectiveness throughout the experiment